Parent perceptions of participation in a parent-mediated communication-focussed intervention with their young child with autism spectrum disorder. (November 2020) - Leadbitter, Kathy; Macdonald, Wendy; Taylor, Carol; Buckle, Karen Leneh; ,
Paediatric Autism Communication Therapy is a parent-mediated, video-aided, communication-focussed intervention for young children with autism spectrum disorder. It has been shown in a UK randomised controlled trial to lead to improvements in parent–child communication and family quality of life, together with a sustained reduction in child autism symptom severity. This qualitative study examined parental perceptions of their participation in Paediatric Autism Communication Therapy within the context of the randomised controlled trial. Semi-structured interviews were carried out with 18 parents within 12 months of completion of the therapy. The thematic analysis provides insights into parents' hopes, expectations, and learning processes when working with Paediatric Autism Communication Therapy therapists and carrying out daily practice in the home. Parents reported positive changes in their interaction and relationship with their child and improvements to their child's communication and interaction. Some also highlighted poignant realisations and emotional challenges associated with taking part in this post-diagnostic therapy. Practical difficulties were also emphasised. Implications for the clinical practice of parent-mediated interventions with young children with autism spectrum disorder are discussed. Lay abstract: Paediatric Autism Communication Therapy is an intervention for young children with autism spectrum disorder that focuses on parent–child communication. In Paediatric Autism Communication Therapy, the therapist and parent watch videos of the parent and child playing together. The therapist coaches the parent to carefully observe the child's communication and to interact with their child in a more sensitive and responsive way. Parents are encouraged to use the strategies with their child at home. Paediatric Autism Communication Therapy has been shown to lead to long-term improvements in parent–child communication and family quality of life. This study aimed to explore parents' perceptions of their participation in Paediatric Autism Communication Therapy. Interviews were carried out by an independent researcher with 18 parents. Parents discussed the learning processes they went through when working with Paediatric Autism Communication Therapy therapists and carrying out home practice. Some parents described initial doubts about the approach and hesitations about being videoed and analysing video material. In time, most parents came to really value the therapy and their relationship with the therapist. They reported positive changes in their interaction and relationship with their child and improvements to their child's communication and interaction. Some also highlighted poignant realisations and emotional challenges associated with taking part in this post-diagnosis therapy. Practical difficulties were also emphasised, including the time commitment, accessibility of therapy venues and difficulties in occupying the child during therapist–parent discussion. Implications for the clinical practice of parent-mediated interventions are discussed.